Customer bera vioural intention towards 100% digital water bill payment: a case of Ranhill SAJ Mersing agency / Sofiah Amir Husain, Erni Mohamad Shah and Sheery Hazmah Yasib - Amir Husain, Sofiah; Mohamad Shah, Erni; Yasib, Sheery Hazmah (2023)
The digital payment system has grown rapidly every year. With each passing year, it gets more integrated into customer daily lives, providing ease and efficiency. Adopting digital payments has become critical for businesses in order to remain competitive and move forward. Despite widespread usage and benefits, there are still sceptics who cite security and risk concerns. Data breaches and privacy concerns are undeniably major challenges in the _digital era. It is worth noting, however, that payment companies have been aggressive in resolving these difficulties. They have included additional security features into their digital payment systems to reduce and, in some cases, eliminate transaction risks. Digital payment platforms include rigorous security features such as encryption methods, multi-factor authentication, and tokenization approaches. Research was done to acquire a better knowledge of customer behaviour toward digital payment systems. The study's goal was to investigate the factors that influence customers' behavioural intentions to use digital payment systems, as well as the relationship between behavioural intention and perceived ease of use, perceived usefulness, perceived security, and perceived risk. The quantitative technique was used in the study methodology, which involved the distribution of printed questionnaires to 301 respondents who made over-the-counter water bill payments at the Ranhill SAJ Mersing Agency on a regular basis. The study aims to shed insight on the motives and concerns that impact customers' decision-making processes when it comes to adopting digital payment systems by evaluating these elements and their interplay. Finally, a thorough grasp of these issues may assist payment providers in further improving their offers and alleviating any residual questions or worries that consumers may have.